Sistem Pendukung Keputusan untuk Seleksi Penerima Beasiswa di Fakultas Teknik Universitas Mataram. - Karinda Irianti; Ario yudo Husodo; Budi Irmawati (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2019)
Scholarships are one of the important components in the education system which aims to provide motivation for students to continue their studies and improve achievement. At present the selection of scholarship admissions in the technical faculty of the University of Mataram still uses manual methods. Information system selection scholarship selection aims so that the selection process for receiving scholarships can be stored neatly and effectively. The application of the scholarship recipient selection process through a computerized system will improve the accuracy of the recipient in accordance with the targets or criteria set. The system is based on applicable rules or criteria. The results of the study can be useful to assist the selection process for receiving scholarships. This scholarship recipient information system has a 62% accuracy rate in the selection process in 150 student data.